O papel do professor nos anos 80: uma análise a partir da reflexão de Florestan Fernandes - Vieira, Carlos Roberto (1995)
This study aims to understand the formation and the role of the teacher, in his theory and practice, as an intellectual within his field of work, and to see how the interference of this practice can contribute to the transformation of society. For this, we used the discourse addressed in the specific works on education, by the intellectual and politician Florestan Fernandes, as well as the Gramscian studies on hegemony, the organic intellectual and the philosophy of praxis. The 1980s was considered mainly due to the effervescence of the changes that occurred in the historical context, in economic, social and political terms, at that time, both at the international and national levels. In this perspective, therefore, we sought to discuss and rethink about teacher training courses, as intellectuals and researchers.